Critical Analysis of e-retailing and the use of the virtual environment by luxury fashion brands - Hay, Justine (2010)
Within the last 5 years, independent researches on fashion luxury market have been focused on the outstanding growth of online shopping. Given the economic turmoil the world is going through, luxury, until recently, did not witness particular impact on its sales. But in 2009, the sector registered a drop in 9% of its benefits, leading to a retreat to the core values and a brainstorming to find ways to counteract the decrease. Parallel to the economic crisis, consumers have fully embraced the digital age and have changed their consumption patterns: they are more tech-savvy users, blog followers and time-savers. While independent online fashion luxury companies are reaping the fruits of their bet, fashion luxury brands have not yet understood the interest of providing an enhanced online experience and selling online. This study aims at analysing if fashion luxury websites have caught up with the digital trends and if their websites are in tune with luxury consumers’ expectations and needs. A content analysis of 50 fashion luxury websites was led alongside a web-based survey. Findings show that generally speaking websites are not providing a complete, consistent and extraordinary experience online. Their online boutique is often limited to accessories or to their premium brands’ outfits whereas respondents clearly advanced their will to be able to shop the whole collection. Cultural differences have also been highlighted among websites’ design and users’ expectations which makes it more difficult for fashion luxury brands to build a website on a global scale. Findings led to managerial implications useful for fashion luxury brands’ managers as well as further research recommendations as this topic is still at its beginning.